T(x) ™: An Approach and Philosophy to Advance Translation to Transformation - Henry Akintobi, Tabia (Ethn Dis, 2019)
The translational science spectrum consists of phases or types of research, from discoveries that advance our understanding of the biological basis of health and disease to interventions that engage individuals and social systems toward improved population health. The health research system has widely acknowledged flaws that delay (or even deny) the fruits of research findings for the population and for chronically disadvantaged groups. Coined and patented at Morehouse School of Medicine (MSM), T(x) ™;symbolizes an approach and scientific philosophy that intentionally promotes and supports the convergence of interdisciplinary approaches and scientists to stimulate exponential advances for the health of diverse communities. While the T(x) ™ patent is new, this approach to research translation is embedded within the MSM tapestry with historically aligned research from the Translational Collaborative Center exemplars as well as newly funded scholars. T(x) ™ scholarship is characterized by the five tenets and practices that ultimately culminate in the conduct of research with results that broaden the evidence-base through data-driven proof of impact on health equity in underserved or special populations. T(x) ™ is a destination that is ever-evolving and responsive to the research, priority populations and partners through translational research and corresponding approaches that transform health, thereby advancing health equity.